Self-Report Motor Competence in Adolescents Aged 12–18 Years in Regional and Rural Victoria (Australia). Issue 3 (3rd July 2021) - Plumb, Mandy S.; Hands, Beth; McIntyre, Fleur; Timler, Amanda
ABSTRACT: Background : Poor motor skills are an increasing issue for adolescents in our local communities. In regional Victoria, almost 20% of children starting school in 2018 were considered at risk or developmentally vulnerable in the domain of physical health and wellbeing. Purpose : The aim of the current study was to examine factors (how adolescents perceive their fine and gross motor skills, activities of daily living, comparison to peers) of motor competence that may be important to adolescents in regional Victoria, Australia, using the Adolescent Motor Competence Questionnaire (AMCQ). Methods : A sample of 183 Australian adolescents ([138 females ( Mage   = 15.59 years, SD  = 1.56); 45 males, ( Mage   = 15.82 years, SD  = 1.95); 12–18 years old] completed the AMCQ. Results : The mean AMCQ score was 87.86 ( SD  = 7.55), with no significant difference between males ( M = 89.67 SD  = 7.29) and females [ M = 87.28 SD  = 7.56; t (181 = 1.86 p =.065)]. A Principal Component Analysis (PCA), extracted five factors (Eiqenvalue of 1.389) explaining 43.46% of variance, representing, Ball Skills and Kinesthesis; Activities of Daily Living; Fine Motor and Gross Motor; Proprioception and Exteroception; Public Performance . Conclusion : The results highlight key factors important in describing an adolescent's motor competence within regional Victoria. With physical health a priority in local communities, understanding these factors is an important first, that which may inform development of physical activity interventions for adolescents.